'I shall prosecute a ruthless war on these monsters … ': a critical metaphor analysis of discourse of resistance in the rhetoric of Kwame Nkrumah. Issue 2 (15th March 2019) - Nartey, Mark
ABSTRACT: In recent years, studies on discourses of resistance in politics have become prevalent, focusing mainly on the language of radical movements and rebel groups, but not the discourses on colonialism, imperialism, and repression which can be considered as potential sites for discourses of resistance. To fill this gap, this paper critically explores how an independence leader utilized metaphor to construct a discourse of resistance against colonialism and imperialism. It analyzes a number of speeches delivered by Kwame Nkrumah, a pioneering Pan-African and Ghana's independence leader, using a combination of models, including critical metaphor analysis and membership categorization analysis. The analysis illustrates that Nkrumah deployed war/conflict/military and religious metaphors in conjunction with other discursive strategies such as labeling or stereotyping, category work, sentimentalism, victim-playing, and negative other-presentation to formulate a resistance discourse against colonialism and imperialism. These metaphors were exploited through representations of (e)vilification, enemification, demonization, freedom and justice, and attack and defense. This paper provides insight into the use of language in the service of resistance and activism, thereby demonstrating that the use of metaphor by political actors serves manipulative and/or ideological purposes (rather than achieving a literary/stylistic effect) and illustrating that metaphor is essential to a leader's persuasive force.